Characterization of Lipopolysaccharides of Bradyrhizobium japonicum KDR 15 Heavy Metal Tolerant - ALFI DATIN ZAUQIAH; TEDJA -IMAS; DWI NINGSIH SUSILOWATI (HAYATI Journal of Biosciences, 2006)
The lipopolysaccharide (LPS) of Bradyrhizobium japonicum KDR 15 heavy metal tolerant strain was isolated by miniphenol-water extraction and yielded LPS in phenol and water phase. The LPS KDR 15 was further characterized by sodium dodecyl sulfate-polyacrilamide gel electrophoresis (SDS PAGE) and showed many bands distributed from an area of high until low molecular weight (LPS IA, IB, and II). Composition analysis of the LPS had been done after acetic acid 1% hydrolysis. The polysaccharide portion consist of glucose, sucrose, galactose, mannose, xylose, arabinose, rhamnose, ribose, glucosamine, and 3-deoksi-D-manno-oktulosonat (KDO). Lipid A portion consisted of C16:0 and C18:1. The LPS also contained 0.02% of protein and 1.7% of phosphate. The presence of functional groups that shows negative charge densities such as phosphate and carboxyl within LPS KDR 15 assumed to be a potentially binding sites for accumulating heavy metals. Key words: Bradyrhizobium japonicum, heavy metal tolerant, lipopolysaccharides